2009
DOI: 10.1503/cmaj.081180
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of insulin analogues for diabetes mellitus

Abstract: Insulin agents available for the treatment of diabetes mellitus include conventional insulins and insulin analogues. Insulin analogues were developed to mimic more closely the separate bolus and basal components of insulin secretion.1 Rapid-acting (bolus or mealtime) and longacting (basal or background) analogue formulations are available. This new class of drugs has been promoted as providing more flexible treatment schedules and a reduced risk of hypoglycemia relative to conventional insulins. 1The cost of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 33 publications
0
101
1
3
Order By: Relevance
“…(16) The results of our economic analysis are in line with the findings from some of these previously published cost-utility analyses, which found that iDet was cost effective compared to iNPH (ICERs: £2,500, £3,443, £9,526, £12,989 and £19,285 per QALY gained), (18;20;42-44) iGlarg was cost effective compared to iNPH (ICERs: £3,496 -£4,978, £3,189 -£9-767 and £10,903 per QALY gained), (45)(46)(47) and one study finding that iDet was dominant (less costly and more effective) over iGlarg. (44) However, this last analysis and ours conflict with that of Cameron and colleagues, (16) which concluded that iGlarg dominated iDet. This is likely to be due to two main reasons.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…(16) The results of our economic analysis are in line with the findings from some of these previously published cost-utility analyses, which found that iDet was cost effective compared to iNPH (ICERs: £2,500, £3,443, £9,526, £12,989 and £19,285 per QALY gained), (18;20;42-44) iGlarg was cost effective compared to iNPH (ICERs: £3,496 -£4,978, £3,189 -£9-767 and £10,903 per QALY gained), (45)(46)(47) and one study finding that iDet was dominant (less costly and more effective) over iGlarg. (44) However, this last analysis and ours conflict with that of Cameron and colleagues, (16) which concluded that iGlarg dominated iDet. This is likely to be due to two main reasons.…”
Section: Discussioncontrasting
confidence: 73%
“…(15)(16)(17)(18)(19)(20) Three found that iDet was less costly and more effective; . (17)(18)(19) while the other two found that iDet was more costly and more effective.…”
Section: Introductionmentioning
confidence: 99%
“…Cameron and Bennett found that the cost effectiveness of insulin analogues depends on the type of insulin analogue that the individual receives and the type of diabetes that is being treated. Based on a comprehensive evaluation of the limited financial resources for health, insulin analogues, from the point of view of glycemic control, do not represent the best clinical or financial option (Cameron and Bennett, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…21 In this analysis, insulin glargine was dominant compared with NPH insulin, i.e., more effective and cost saving. Cameron and Bennett 22 conducted a CUA from the perspective of the Canadian health care system. They included symptomatic and severe hypoglycemia and their effects on quality of life, including fear of hypoglycemia, and examined the treatment costs.…”
Section: Discussionmentioning
confidence: 99%